Human ceruloplasmin and neurotransmitters: complex stabilization and crystallization - Moutinho, Daniela Mesquita (2013)
Dissertation to obtain a Master Degree in Molecular Genetics and Biomedicine at Faculty of Sciences and Technology,Universidade Nova de Lisboa